Biallelic novel missense HHAT variant causes syndromic microcephaly and cerebellar‐vermis hypoplasia. Issue 6 (26th March 2019) - Abdel‐Salam, Ghada M. H.; Mazen, Inas; Eid, Maha; Ewida, Nour; Shaheen, Ranad; Alkuraya, Fowzan S.
Abstract : We report two siblings with microcephaly, early infantile onset seizures, and cerebellar vermis hypoplasia, in whom whole exome sequencing revealed a novel homozygous missense (c.770T>C, p.[Leu257Pro]) variant in the hedgehog acyl‐transferase gene ( HHAT ), encoding an enzyme required for the attachment of palmitoyl residues that are critical for multimerization and long and short range hedgehog signaling. There is a report of one family with Nivelon–Nivelon–Mabille syndrome in which HHAT was proposed as the likely candidate gene. The phenotypic overlap with the family we report herein provides further evidence implicating HHAT in cerebellar development and the pathogenesis of this rare spectrum.